The Macaronesian endemic moss Andoa berthelotiana (Myuriaceae, Bryophyta): Phylogenetic relationships and cryptic speciation - Martins, Soraia (2021)
The Macaronesian endemic pleurocarpous moss species Andoa berthelotiana occurs in the Madeira, Azores and Canary Islands archipelagos. It has a checkered taxonomic history with placements in different genera or, as monospecific genus Andoa, in different families, most frequently in the Hypnaceae. Earlier molecular phylogenetic analyses indicated a close relationship of Andoa with Ctenidium, Hyocomium and Myurium in a clade corresponding to Myuriaceae, which was supported in the present study based on a larger sampling and markers from all three genomes (chloroplast trnL-trnF, nuclear ribosomal ITS and mitochondrial nad5). Haplotype networks of the nad5 and ITS sequences as well as AFLP fingerprinting data revealed the existence of two intraspecific lineages in Andoa berthelotiana, one occurring in Madeira and the Canary Islands and the other in the Azores. The trnL-trnF haplotype network contradicts this geographic pattern, however, the position of the two mutations differentiating the trnL-trnF haplotypes suggests that they may not be phylogenetically informative. A detailed morphological analysis of plants from the Azores and Madeira indicates the existence of distinguishing characters that correspond with the two molecular lineages. However, the considerable morphological overlap observed would hamper the identification of specimens if both lineages were formally described as separate taxa. We therefore suggest treating the two lineages of Andoa as semi-cryptic species.